Altered Cytotoxicity Profile of CD8+ T Cells in Ankylosing Spondylitis. Issue 3 (22nd January 2020) - Gracey, Eric; Yao, Yuchen; Qaiyum, Zoya; Lim, Melissa; Tang, Michael; Inman, Robert D.
Abstract : Objective: Ankylosing spondylitis (AS) is an inflammatory arthritis in which men have a higher risk of developing progressive axial disease than women. Transcriptomic studies have shown reduced expression of cytotoxic cell genes in the blood of AS patients. HLA–B27 contributes the greatest risk for AS, suggesting a role for CD8+ T cells. This study was undertaken to profile AS patient cytotoxic cells with the hypothesis that an alteration in CD8+ T cells might explain the aberrant cytotoxic profile observed in patients. Methods: Whole blood was examined for GZM and PRF1 gene expression by quantitative polymerase chain reaction. Serum and synovial fluid (SF) were examined for granzyme and perforin 1 expression by bead array, and blood and SF mononuclear cells were examined for granzyme and perforin 1 expression by fluorescence‐activated cell sorting (FACS). Results: GZM and PRF1 gene expression were both reduced in AS patients compared to healthy controls, especially in men. Perforin 1, but not granzyme, protein levels were reduced in AS patient serum. Granzymes were elevated in AS SF, but not in rheumatoid arthritis or osteoarthritis SF. FACS revealed a reduction in granzyme‐positive and perforin 1–positive lymphocytes, but not an intrinsic defect in CD8+ T cell granzyme or perforin 1 production. CD8+ T cell frequency was reduced in the blood and increased in the SF of AS patients. Conclusion: Our findings indicate that AS patients have an altered cytotoxic T cell profile. These data suggest that CD8+ T cells with a cytotoxic phenotype are recruited to the joints, where they exhibit an activated phenotype. Thus, a central role for CD8+ T cells in AS may have been overlooked and deserves further study.